Association between serum albumin creatinine ratio and all-cause mortality in intensive care unit patients with heart failure - Wang, Jiuyi; Li, Ni; Mu, Yunkai; Wang, Kai; Feng, Guibo (Frontiers in Cardiovascular Medicine, 2024)
The serum albumin creatinine ratio (sACR) has been established as a potential indicator for heart disease, however, its relationship with prognosis in intensive care unit (ICU) patients with heart failure remains uncertain. This study aimed to investigate the association between sACR levels and all-cause mortality ICU patients with heart failure.Methods: Clinical data from MIMIC-Ⅳ database was utilized for the analysis of ICU patients with heart failure.Patients were categorized into quartiles (Q1-Q4) based on sACR levels. Kaplan-Meier survival analysis and multivariate adjusted Cox regression models were employed to assess the association between sACR levels and mortality outcomes within 365 days. Subgroup analysis was used to evaluate the prognostic impact of sACR across diverse populations. Restricted cubic spline curves and threshold effect analysis were utilized to quantify the doseresponse relationship between sACR levels and risk of all-cause mortality. Mediating effects analysis was conducted to present the involvement of albumin and creatinine in the association between sACR and outcomes.The analysis encompassed a cohort of 4506 patients, with Kaplan-Meier curves indicating that individuals with lower sACR levels exhibited an elevated risk of all-cause mortality (log-rank p<0.001). Multivariate adjusted Cox regression and subgroup analysis demonstrated that individuals in Q2 (hazard ratio (HR) 0.82, 95%CI 0.71 0.96), Q3 (HR 0.76, 95%CI 0.64 0.91) and Q4 (HR 0.62, 95%CI 0.50 0.76) had a decreased risk of mortality compared to individuals in Q1 (lower levels of sACR) (p for trend < 0.001), and this inverse relationship was consistently observed across various subgroups. Subsequent restricted cubic spline analysis revealed a negative yet nonlinear relationship between sACR and all-cause mortality (p for nonlinear < 0.001), and threshold effect analysis indicated an effect threshold of 3.75. Additionally, mediating effects analysis emphasized that sACR influenced the outcome not only through serum albumin and creatinine pathways, but also through direct mechanisms.The study found that low levels of sACR were independently associated with an increased risk of one-year all-cause mortality in ICU patients with heart failure, with a threshold effect, which could potentially serve as an early warning indicator for high-risk populations.